Reference Points and the Tradeoff between Risk and Incentives - Thomas Dohmen; Arjan Non; Tom Stolp (Institute of Labor Economics (IZA), 2021)
We conduct laboratory experiments to investigate basic predictions of principal-agent theory about the choice of piece rate contracts in the presence of output risk, and provide novel insights that reference dependent preferences affect the tradeoff between risk and incentives. Subjects in our experiments choose their compensation for performing a real-effort task from a menu of linear piece rate and fixed payment combinations. As classical principal-agent models predict, more risk averse individuals choose lower piece rates. However, in contrast to those predictions, we find that low-productivity risk averse workers choose higher piece rates when the riskiness of the environment increases. We hypothesize that reference points affect piece rate choice in risky environments, such that individuals whose expected earnings would exceed (fall below) the reference point in a risk-free environment behave risk averse (seeking) in risky environments. In a second experiment, we exogenously manipulate reference points and confirm this hypothesis.
Keywords: D81; D91; M52; 330; incentive; piece-rate; risk; reference point; laboratory experiment